Do share prices lead economic activity in emerging markets? Evidence from South Africa using Granger-causality tests. Issue 3 (3rd July 2017) - Sayed, Ayesha; Auret, Christo; Page, Daniel
ABSTRACT: The forward-looking characteristic of share prices and their subsequent role as leading indicators of economic activity has been widely documented in advanced economies, with evidence in emerging countries being less prevalent. This paper investigates the information content of share prices as a leading indicator in South Africa using both nominal and real quarterly and monthly time-series data for the period March 1998 to December 2016. Taking market segmentation on the JSE into account, causality between the All-Share index, the Industrial index, the Resources index and the Financial index is examined against GDP and industrial production using the test proposed by Granger (1969 ). The empirical investigation reveals overwhelming evidence in favour of the JSE as a leading indicator of economic activity, as unidirectional causality is established between the four market segmentation proxies and the macroeconomic variables.